OPTIMALISASI PELAKSANAAN POS PEMBINAAN TERPADU JANTUNG (POSBINDU JANTUNG) DI DESA BAJO INDAH KECAMATAN SOROPIA KABUPATEN KONAWE - Banudi, La; Toruntju, Sultan Akbar; Rofiqoh (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2025)
Heart disease usually occurs due to damage to the heart muscle cells in pumping blood flow throughout the body. This disease can be prevented by minimizing risk factors including unhealthy diet, lack of physical activity, cigarette consumption, and increased stressors and exposure to causes. This activity aims to optimize the implementation of the Integrated Heart Development Post (Posbindu Jantung) in Bajo Indah Village. The implementation of community service activities uses the Participatory Action Research (PAR) method. Preparation for activities carried out is program coordination to the Soropia Health Center, the results of the implementation of the Posbindu Jantung training are that the level of knowledge of cadres has increased based on the results of the pre and post tests. The level of cadre skills has also increased. The results of the screening were mostly normal blood pressure category 60%, normal body mass index category 80%, and obese waist circumference category 55%. Evaluation was held post-test with an increase of 3.8%. Optimization was carried out in the implementation of Cadre activities. The suggestion submitted was Cross-sector cooperation between the local government and the Health Center in terms of providing facilities and infrastructure for the smooth running of the PTM posbindu activities. The suggestions given are to increase the capacity of cadres through further training, provide more adequate resources, and increase educational efforts on an ongoing basis.